2022
DOI: 10.1111/jocn.16471
|View full text |Cite
|
Sign up to set email alerts
|

Persistent symptoms among post‐COVID‐19 survivors: A systematic review and meta‐analysis

Abstract: BackgroundSingle studies support the presence of several post‐COVID‐19 symptoms; however, there is no evidence for the synthesis of symptoms.ObjectiveWe attempt to provide an overview of the persistent symptoms that post‐COVID‐19 patients encounter, as well as the duration of these symptoms to help them plan their rehabilitation.DesignSystematic review and meta‐analysis.ParticipantsA total of 16 studies involving 8756 patients post‐COVID‐19 were included.MethodsThe CINAHL, PubMed, EMBASE, Scopus, and Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 68 publications
0
16
0
1
Order By: Relevance
“…The present study showed the resolution of loss of taste sensation as their results showed that patients treated with diode laser 940 have a significantly higher percentage of cases 13(72.2%) restoring taste after one week. Rochmawati and Kamilah [ 27 ] proposed that the persistence of symptoms in COVID-19 patients was attributed to the overexpression of mitochondrial proteins and the presence of inflammatory markers. In addition, they found increased pro-inflammatory cytokines that could contribute to cytokine dysregulation and a cytokine storm.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed the resolution of loss of taste sensation as their results showed that patients treated with diode laser 940 have a significantly higher percentage of cases 13(72.2%) restoring taste after one week. Rochmawati and Kamilah [ 27 ] proposed that the persistence of symptoms in COVID-19 patients was attributed to the overexpression of mitochondrial proteins and the presence of inflammatory markers. In addition, they found increased pro-inflammatory cytokines that could contribute to cytokine dysregulation and a cytokine storm.…”
Section: Discussionmentioning
confidence: 99%
“…2 Cough and fatigue were the most common symptoms in the present population, a finding in agreement with an Indian study, 4 which was the only study during the Omicron wave that showed data for each symptom. These symptoms were also common during pre-Omicron waves, 9 suggesting a similarity of major symptoms of long COVID irrespective of the timing of infection.…”
mentioning
confidence: 88%
“…Withcommitmenttosharing,learningfromandbuildingonour international experiences, perhaps we will be better prepared to Research and reviews about the longer-term impact of COVID-19 on patients-paediatric to geriatric, pulmonary to cardiac, ICU to nursing home, reveal post-acute sequelae (PASC), including persistent physical symptoms (Allgood et al, 2021;Cha &Baek,2021;Jainetal.,2023;Lambertetal.,2021;Rochwamati et al, 2022;Wu et al, 2022) and long-term psychological consequences (Bilginetal.,2021;DelCorraletal.,2022)includingposttraumatic stress (Fjone et al, 2023)-these topics and more are includedinthisissue.…”
Section: E D I T O R I a L The Long-term Impact Of Covid-19mentioning
confidence: 99%